RESENHA - LE LANGAGE... - Hegenberg, Leonidas (Reflexão, 1998)
Brigitte Frelat-Kalm. LELANGAGE, Paris, Editions Quintette, 1995, 63 páginas (coleção "Philosopher", formato bolso, $8,96 francos franceses)